2018
DOI: 10.1242/jcs.221481
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of sperm membrane proteins CMTM2A and CMTM2B is essential for ADAM3 localization and male fertility in mice

Abstract: Chemokines are signaling proteins that are secreted to induce chemotaxis during an immunological response. However, the functions of transmembrane-type chemokine-like factor (CKLF) and the CMTM (CKLF-like MARVEL transmembrane domain containing) protein family remain to be determined. In this study, we focused on the testis-specific mouse CMTM gene cluster (, and) and generated CRISPR/Cas9-mediated mutant mice to examine their physiological functions. Although mutant mice were fertile, and double mutant mice ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…indeed affected the localization of ADAM3 (Fujihara, Oji, et al, 2018), which is essential for male fertility (Okabe, 2018). Interestingly, CMTM2B disappeared from sperm in Adam3-deficient mice, while CMTM2A remained.…”
Section: Testis-specific Serine Proteases (Prss3and Prss55)mentioning
confidence: 96%
See 4 more Smart Citations
“…indeed affected the localization of ADAM3 (Fujihara, Oji, et al, 2018), which is essential for male fertility (Okabe, 2018). Interestingly, CMTM2B disappeared from sperm in Adam3-deficient mice, while CMTM2A remained.…”
Section: Testis-specific Serine Proteases (Prss3and Prss55)mentioning
confidence: 96%
“…Cmtm1 mutant males were fertile, Cmtm2a and Cmtm2b double mutant male mice were sterile due to impaired sperm function (Fujihara, Oji, et al, 2018). Immunostaining indicated that CMTM2A and CMTM2B were localized to the plasma membrane on the sperm head (Fujihara, Oji, et al, 2018).…”
Section: Testis-specific Serine Proteases (Prss3and Prss55)mentioning
confidence: 99%
See 3 more Smart Citations